2021
DOI: 10.1155/2021/5573650
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid LSTM-Based Ensemble Learning Approach for China Coastal Bulk Coal Freight Index Prediction

Abstract: China Coastal Bulk Coal Freight Index (CBCFI) reflects how the coastal coal transporting market’s freight rates in China are fluctuated, significantly impacting the enterprise’s strategic decisions and risk-avoiding. Though trend analysis on freight rate has been extensively conducted, the property of the shipping market, i.e., it varies over time and is not stable, causes CBCFI to be hard to be accurately predicted. A novel hybrid approach is developed in the paper, integrating Long Short-Term Memory (LSTM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In the study of time series prediction, many papers have shown that LSTM has obvious advantages.Kim et al [ 24 ] found that LSTM can effectively improve the prediction performance of BDI by comparing time series analysis and deep learning methods. In a study by Xiao et al [ 25 ], they combined LSTM and integrated learning techniques to forecast CBCFI, which outperformed other methods when dealing with information involving dramatic market downturns. In stock market research, Nelson et al [ 26 ] proposed a stock price prediction model based on LSTM, which was used to simulate transactions and compared with the benchmark model to evaluate its prediction performance.…”
Section: Related Workmentioning
confidence: 99%
“…In the study of time series prediction, many papers have shown that LSTM has obvious advantages.Kim et al [ 24 ] found that LSTM can effectively improve the prediction performance of BDI by comparing time series analysis and deep learning methods. In a study by Xiao et al [ 25 ], they combined LSTM and integrated learning techniques to forecast CBCFI, which outperformed other methods when dealing with information involving dramatic market downturns. In stock market research, Nelson et al [ 26 ] proposed a stock price prediction model based on LSTM, which was used to simulate transactions and compared with the benchmark model to evaluate its prediction performance.…”
Section: Related Workmentioning
confidence: 99%
“…The size of the facility depends on knowing the green H 2 demand beforehand, and this demand is directly correlated with the freight rates, and the vessels’ dead weight ton (DWT). However, freight rates are uncertain and unstable over time, mainly due to variation in the property of the shipping market, geopolitical situation, weather conditions, global supply demand, etc. Increasing literature proposes multistep prediction approaches to forecast freight rates using time series models, mainly including the Auto-Regressive model (AR), the Auto-Regressive Integrated Moving Average model (ARIMA), and their variants .…”
Section: Introductionmentioning
confidence: 99%
“…So, it can, to a certain extent, reflect the economic development of China and the trend of coastal bulk trade. The release of CBCFI helps the development of the shipping index system in the China coastal coal transportation market [4]. As the "barometer" of the coastal coal transportation market, the index can accurately and timely reflect the dramatic and frequent price fluctuations in the coastal coal transportation market [5].…”
Section: Introductionmentioning
confidence: 99%